2002
DOI: 10.4049/jimmunol.169.5.2430
|View full text |Cite
|
Sign up to set email alerts
|

TheDermatophagoides pteronyssinusGroup 2 Allergen Contains a Universally Immunogenic T Cell Epitope

Abstract: The use of T cell epitope-containing peptides for the induction of anergy in allergen sensitization is limited by genetic restriction that could be circumvented by using universally immunogenic epitopes. We attempted to identify such epitopes on Dermatophagoides pteronyssinus group 2 allergen (Der p 2), a major allergen of D. pteronyssinus T cells from BALB/c (H-2d), C57BL/6 (H-2b), C3H (H-2k), and SJL (H-2s) mice that were immunized with rDer p 2, recognized an immunodominant region encompassing residues 21–3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 33 publications
3
16
0
Order By: Relevance
“…The latter finding reconciles the results presented here with the X-ray crystallographic studies of Johannessen et al [14], who used ammonium sulphate precipitation. In the study by Wu et al [13], using undisclosed monoclonal antibodies to validate the structure of their rDer p 2 secreted from P. pastoris, the binding of these antibodies would be consistent with the observation here, i.e. even in the absence of the natural secondary structure, the IgE binding of rDer p 2 secreted from P. pastoris was largely intact.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…The latter finding reconciles the results presented here with the X-ray crystallographic studies of Johannessen et al [14], who used ammonium sulphate precipitation. In the study by Wu et al [13], using undisclosed monoclonal antibodies to validate the structure of their rDer p 2 secreted from P. pastoris, the binding of these antibodies would be consistent with the observation here, i.e. even in the absence of the natural secondary structure, the IgE binding of rDer p 2 secreted from P. pastoris was largely intact.…”
Section: Discussionsupporting
confidence: 68%
“…Firstly, rDer p 2 was prepared by a single gel filtration step according to Wu et al [13]. Secondly, the allergen from this preparation was precipitated with 10% trichloro-acetic acid (TCA) and redissolved in PBS.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…p21-35 has been extensively studied in our laboratory: it contains both a major promiscuous T cell epitope and a dominant B epitope (17), thereby providing a suitable sequence for the study of tolerance induction at B and T cell levels. Injection of p21-35 in conventional adjuvant elicits strong specific Ab responses, while the same peptide under tolerogenic conditions results in prevention and partial suppression of the immune response toward Der p 2 (18).…”
Section: In Vivo Induction Of Type 1-like Regulatory T Cells Using Gementioning
confidence: 99%
“…We have previously demonstrated that p21 contained a promiscuous T cell epitope that was able to bind to MHC class II alleles of at least four different mouse haplotypes (33). Ile 28 in the p21 sequence was shown to act as a major MHC class II anchoring residue for each mouse strain.…”
Section: Wehi Cell Lysis Depends On Cognate Interaction With P21 Bounmentioning
confidence: 99%